A dynamic smoke generation and nose-only inhalation exposure system for rats: preliminary results from studies of selected transportation materials. (December 2014) - Sun, Lei; Zhao, Xiaolong; Li, Daibo; Cai, Ying; An, Hui; Wang, Tao; Cui, Zhihong; Yang, Huan; Han, Fei; Ao, Lin; Liu, Jinyi; Cao, Jia
Abstract Context: Smoke inhalation injury is the main cause of fatalities for fire victims. Understanding in the pathophysiology of the injury has not been fully explored in recent years. To further explore the pathophysiological mechanism, a dynamic and controllable animal model is necessary. Objective: To develop a rat model of smoke inhalation injury to simulate human victims in air-restricted vehicle cabin fires. Materials and methods: Smoke concentration, including CO, O2, VOCs and smoke temperature under different combustion conditions, were detected. Levels of COHb, respiratory function, lung wet-to-dry weight ratio and protein concentration in BALF and blood were measured. Pathological evaluations of lung in tissues were conducted at 1, 6, 24 and 48 h post-exposure. Results: Smoke concentration rose with the increase of combustion temperature and decrease of oxygen flow. Further, 215 kinds of VOCs in the smoke were detected, and the concentrations of benzene, methylbenzene, ethylbenzene, dimethylbenzene, phenylethylene and trimethylbenzene was 32.93, 402.06, 764.03, 113.73, 1006.61 and 89.28 mg/m3, respectively. Significant hypoxemia and CO poisoning occurred in rats. The FCOHb after exposure for 14 min immediately rose to (44.2 ± 12.3) % and then gradually decrease to a normal level at 300 min post-exposure. At 24 h post-exposure, Penh increased significantly (p < 0.05), and high pulmonary vascular permeability and significant lung edema (p < 0.05) were observed in the smoke inhalation group. Discussion and conclusion: In summary, the novel rat model of smoke inhalation injury system used in the study is dynamic and controllable, and appropriate for use in smoke inhalation injury studies of air-restricted cabins in vehicles.